Pembinaan Peningkatan Kesadaran Orang Tua Terhadap Pendidikan Anak Melalui Kolom Kamrat di Kelurahan Lawangan Daya Pademawu Pamekasan - Afandi, Afandi; Sayyi, Ach.`; Mukit, Abdul; Sopi, Adus (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2023)
Parents in the social community, especially in the era of society 5.0 as it is today, have a great responsibility, because parents have to go the extra mile in maintaining their development, mentality, association, intellect and education, as well as the transformation of moral values and morals, culture and traditions that followed and developed by children, and motivation so that children have good character in the family and in society. Counseling activities for parents in raising awareness of the importance of children's education are carried out using the ABCD (asset-based communities’ development) approach through koloman kamrat (kamrat gathering) activities in Lawangan Daya village. The results of the coaching show that there are implications that change the mindset of parents from education and career only for personal life to be sensitive and fully responsible for all processes of forming their children through education in the family. Coaching activities carried out, through emphasis; 1) aspects of human potential; 2) aspect of social potential; and 3) aspects of cultural and spiritual potential.